Is Tunisia really democratising? Progress, resistance, and an uncertain outlook - Max Gallien; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2019)
January 2019 marked the eighth anniversary of the end of the Ben Ali dictatorship - the celebrations however were marred by massive social protests. Opinions both in Tunisia and abroad differ about the state of Tunisia's political development as it gears up for its second parliamentary and presidential elections since the adoption of the new constitution in 2014. While some consider its democratisation to be virtually complete, others fear a relapse into autocracy. Despite its considerable democratic achievements, Tunisia is in danger of developing into a hybrid system: part democratic, part authoritarian. This is not only due to the difficult economic and regional context. Critically, the political, economic and administrative networks of the old system, as well as persistent authoritarian practices and "old" rhetoric in politics and society, complicate the deepening of its fragile democracy. Tunisia's international partners should make it their explicit objective to weaken these counter-currents.
Keywords: 320